The The Influence of Program Participation on The Empowerment of Sustainable Food Program Participants During The Pandemic Era - Saleh, Amiruddin; Hanifah, Nur (Jurnal Penyuluhan, 2024)
The imposition of large-scale social restrictions has an impact on decreasing participation in empowerment. On the other hand, participation is one of the principles of empowerment. The application of this principle will consequently make the community empowered. Through these stages of empowerment, the community can get out of its powerless condition. If empowerment is realized, the program deserves to be called an empowerment program. This study aims to analyze the influence of program participation on empowerment. The study used the census method on 35 respondents and was supported by qualitative data. Based on the research results, program participation in the planning stage has a positive influence on power within, power to, and power with. Program participation in the decision-making stage has a positive influence on power over. Program participation in the implementation phase has a positive influence on power within, power to, and power with. Monitoring and evaluation have a positive influence on power. Program participation in the outcome utilization stage has a positive influence on power within and power to.